ANALISIS DAMPAK PENERIMAAN PAJAK DAERAH TERHADAP PERTUMBUHAN EKONOMI DAN KETIMPANGAN REGIONAL DI INDONESIA - Drieandita, Kanaya; Santoso, Dwi Budi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Indonesia has a slow rate of economic growth, which is accompanied by a high level of regional inequality. In Indonesia, on the other hand, the tax ratio has decreased from year to year. As a result, more research is needed to determine how taxes affect economic growth and regional equity in Indonesia. This study employs two equation models that are processed using the multiple linear regression method on panel data from 34 Indonesian provinces at the years 2016, 2019, and 2021. The findings of this study show that there is a convergence condition in Indonesia, and the existence of taxes as a government role can accelerate the convergence rate by 0.78%, or up to 27 years. This proves that the tax function as a distribution function has been effective, and convergence is expected to form equity or reduce inequality in Indonesia. Taxation, on the other hand, has been shown to have a positive and significant impact on economic growth. This reveals that the tax function has worked effectively as an allocation function, with taxes being allocated for public expenditures that support productivity.